Issues and impact of COVID-19 on surgical services in Northern Borneo, Sabah - Mohd Firdaus Mohd Hayati; Nik Amin Sahid Nik Lah; Andee Dzulkarnaen Zakaria; Syed Sharizman Syed Abdul Rahim; Nornazirah Azizan (Penerbit UMS, 2022)
Globally, everyone has gone through an unusual and remarkable period during the COVID-19 pandemic. The pandemic has affected various sectors in the country and implicated society. Important services including the health care system, particularly in surgery, have raised challenges and issues that need to be sorted out. This action is prudent to justify the balance in between care on preventing the spread of COVID-19 infection and at the same time providing surgical services. In this article are the perspectives on how we elicit the issues and the solutions in providing surgical services during the COVID-19 pandemic in our state, Sabah.